2022
DOI: 10.1128/mbio.03771-21
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Surveillance of Vancomycin-Resistant Enterococcus faecium Reveals Spread of a Linear Plasmid Conferring a Nutrient Utilization Advantage

Abstract: Sequencing microbial pathogens causing outbreaks has become a common practice to characterize transmission networks. In addition to the signal provided by vertical evolution, bacterial genomes harbor mobile genetic elements shared horizontally between clones.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 98 publications
(127 reference statements)
0
17
0
Order By: Relevance
“…We performed a core genome analysis with 18 plasmids, including pELF1 and pELF2, along with 14 putative pELF1-like plasmids confirmed by a public database search (Fig. 1 and Supplementary Table 4) 9, 15 . At Blastp = 80% (considered to cover most core genes), a rapid large-scale prokaryote pan-genome analysis (Roary) estimated the core genome to consist of 57 CDSs, which was 56.4% of the CDSs in pELF_JHP9 (Supplementary Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a core genome analysis with 18 plasmids, including pELF1 and pELF2, along with 14 putative pELF1-like plasmids confirmed by a public database search (Fig. 1 and Supplementary Table 4) 9, 15 . At Blastp = 80% (considered to cover most core genes), a rapid large-scale prokaryote pan-genome analysis (Roary) estimated the core genome to consist of 57 CDSs, which was 56.4% of the CDSs in pELF_JHP9 (Supplementary Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted September 7, 2022. ; https://doi.org/10.1101/2022.09.07.506885 doi: bioRxiv preprint MGEs, such as plasmids, play an important role in the efficient propagation of drug resistance genes in enterococci. Several reports on enterococcal pELF1-like plasmids have shown that they confer vancomycin resistance and promote carbohydrate availability; although they have a significant impact in clinical practice, their biological effects on the host enterococci are poorly understood 8,9,15 . In this study, we conducted a comprehensive analysis of pELF1-like plasmids based on growth phenotype and transcriptomics coupled with molecular epidemiology.…”
Section: Discussionmentioning
confidence: 99%
“…Whole genome sequencing (WGS) is a powerful tool for studying bacterial adaptation and identifying outbreaks of drug-resistant pathogens. The study by Boumasmoud et al used WGS to sample VREfm at a single Swiss hospital over a 4-year period ( 6 ). Sequencing of 69 VREfm colonizing and invasive isolates collected from 61 different patients uncovered a persistent clone belonging to multilocus sequence type (ST) 203 that was sampled 31 times over 3 years and was responsible for an outbreak of VREfm infection.…”
Section: Commentarymentioning
confidence: 99%
“…We identified a linear plasmid (p2_VRED06-10) carrying vanA in our ST80 reference genome. Boumasmoud et al (36) recently described the linear plasmid pELF_USZ in VREfm from Switzerland that carried an operon conferring the ability to utilise the human gut mucin Nacetyl-galactosamine; however, p2_VRED06-02 did not carry this operon. The advent of long read sequencing has allowed the increasing identification of linear plasmids, and their impact on niche adaptation remains to be fully elucidated (36)(37)(38)(39)(40).…”
Section: Variability In Amr and Mobile Elementsmentioning
confidence: 99%